The Advocacy In Action Study (AIAS): a randomised controlled trial of an advocacy package directed at elected councillors to improve pedestrian safety in high risk deprived neighbourhoods. (1st March 2011) - Lyons, R A; Kendrick, D; Towner, E M; Coupland, C; Hayes, M; Christie, N; Kimberlee, R; Jones, S; Turner, S; Brussoni, M; Groom, L; Macey, S; et al.
Abstract : Objectives: To determine whether an advocacy package aimed at elected councillors resulted in improved pedestrian safety in deprived areas. Methods: Cluster randomised controlled trial involving 617 councillors from 239 wards in England and Wales, from deprived areas with high pedestrian injury rates. The intervention group were provided with information and maps on casualty sites, numbers and effective interventions. Outcomes were measured at 3, 18 and 27 months. Results: The intervention improved short-term outcomes such as increasing councillors interest in child accident prevention (RR 1.09, 95% CI 1.03 to 1.16), increasing belief they could take action to help prevent child accidents (RR 1.36, 95% CI 1.16 to 1.61), and particularly on pedestrian safety (RR 1.55, 95% CI 1.19 to 2.03). By 18 months 63% of intervention councillors reported involvement in supporting new pedestrian road safety schemes. However, pedestrian safety measure changes were statistically non-significant: difference in road length traffic calmed (0.07 km, 95% CI: −0.07 to 0.20); proportion of schools with 20 mph zones (RR 1.47, 95% CI: 0.93 to 2.32), Safe Routes to School (RR 1.34, 95% CI: 0.83 to 2.17; or proportion providing practical pedestrian training (RR 1.23, 95% CI: 0.95 to 1.61). Implications: The AIAS intervention succeeded in raising councillors awareness of and interest in pedestrian safety but failed to improve engineering or educational measures of pedestrian safety. Longer term supported advocacy may be needed for change.